2014
DOI: 10.1007/s00216-014-8083-2
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation and detectability of the designer drug 2,5-dimethoxy-4-propylphenethylamine (2C-P) studied in urine by GC-MS, LC-MS n , and LC-high-resolution-MS n

Abstract: 2,5-Dimethoxy-4-propylphenethylamine (2C-P) is a hallucinogenic designer drug of the phenethylamine class, the so-called 2Cs, named according to the ethyl spacer between the nitrogen and the aromatic ring. The aims of the present work were to identify the phases I and II metabolites of 2C-P. In addition, the detectability of 2C-P and its metabolites in urine as proof of an intake in clinical or forensic cases was tested. According to the identified metabolites, the following pathways were proposed: N-acetylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Of course, depending on species differences, genetic variations, doses, and/or time after administration, diphenidine might also be detected and the panel of metabolites may vary. According to many former studies, combination of rat urine studies with incubations of new drugs with pHLM provides a tool for good predictions of phase I metabolites for detection in human urine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, depending on species differences, genetic variations, doses, and/or time after administration, diphenidine might also be detected and the panel of metabolites may vary. According to many former studies, combination of rat urine studies with incubations of new drugs with pHLM provides a tool for good predictions of phase I metabolites for detection in human urine.…”
Section: Resultsmentioning
confidence: 99%
“…The sample preparation was according to already published studies for lefetamine and its derivatives . A 2‐mL aliquot of urine was adjusted to pH 5.2 with acetic acid and incubated at 56°C for 1.5 h with 30 μL of a mixture (100 000 Fishman units/mL) of glucuronidase/arylsulfatase from Helix Pomatia L. Then, the urine sample was diluted with 2 mL of water, mixed and gradually loaded onto the cation exchange cartridge, which was preconditioned with 1 mL of methanol and 1 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…), are the most studied and described in the literature. Most popular phenethylamines contain methoxy groups in positions 2 and 5 and different lipophilic substituents in position 4 in benzene ring (2C family) …”
Section: Introductionmentioning
confidence: 99%
“…Applying GC/MS to study amphetamines of 2C and NBOMe series (as well as of the metabolites thereof) and to ensure their reliable determination and identification, their acyl and alkyl derivatives are often obtained …”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies showed that the metabolism of rats was qualitatively comparable to that of humans as the rat metabolites could also be detected in authentic human urine from clinical or forensic case work Welter et al 2013Welter et al , 2015bMeyer et al 2013cMeyer et al , 2015Caspar et al 2015;Helfer et al 2015b;Wink et al 2015c).…”
Section: Hrms For Elucidation Of the Metabolite Structures And Formatmentioning
confidence: 99%